The Use Of Value Clarification Technique (VCT) In Improving Pancasila And Civics Education Learning - Eka Setya Septiningrum; Wahyudi Wahyudi; Moh Salimi (Universitas PGRI Semarang, 2020)
The use of Value Clarificatin Technique (VCT) in improving Pancasila and Civics Education Learning about the theme entlitled “Health is Important”. This research is a collaborative Classroom Action Research conducted within two cycles consists of planning, action, observation, and reflection. The data used were in the form of qualitative data, namely the value of the attitude of responsibility and knowledge of the contents of Pancasila and Civics Education learning. The result of this research indicated (1)the use of VCT implemented by the following steps: (a)expositon, (b)presentation of dilemmas, (c)determination of arguments, (d)testing of argument and classification of values, (e)inference, and (f)evaluation; (2)VCT learning model could improve Pancasila and Civics Education Learning as evidenced by an increase in the percentage of completeness in the value of attitude 6,12% and increasing the percentage of completeness of the value of knowledge 8,44%;and (3)the problems encountered, namely: (a)less extensive materials, (b)stimulus didn’t reach the whole class, and (c)timing was less effective; Solutions are: (a)developing material, (b)enlarging the stimulus, and (c)creating effective timing. The conclusion of this research indicated that the use of VCT could improve the attitude and knowledge of the Pancasila and Civics Education content on the theme entitled “Health is Important”.